2007
DOI: 10.2186/prp.6.127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Saliva Secretion on the Assessment of Masticatory Performance

Abstract: This study confirms that the saliva secreted during gummy jelly chewing has an influence on the masticatory performance which was obtained by measuring glucose extraction. AbstractPurpose: The purpose of this experiment was to clarify whether the amount of saliva secreted during the chewing gummy jelly affected the assessment of masticatory performance. Methods:Twenty healthy subjects were asked to chew 2 g of gummy jelly for 10, 15, and 20 seconds and the amounts of glucose extraction and saliva secretion wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…[23][24][25][26][27] Recently, themethodofcalculatingandevaluatingthefoodintakescore(FIS) from the results of questionnaires has been widely used. 12,[28][29][30][31][32][33][34][35][36][37][38][39][40][41] Thus, both objective and subjective methods are used to evaluate masticatory performance, with some studies combining both methods, 2,12,15,24,33,34,37,39,40,42,43 some using only objective methods 1,[3][4][5][6][7][8][9][10]11,14,[16][17][18][19][20][21][22]26,…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[23][24][25][26][27] Recently, themethodofcalculatingandevaluatingthefoodintakescore(FIS) from the results of questionnaires has been widely used. 12,[28][29][30][31][32][33][34][35][36][37][38][39][40][41] Thus, both objective and subjective methods are used to evaluate masticatory performance, with some studies combining both methods, 2,12,15,24,33,34,37,39,40,42,43 some using only objective methods 1,[3][4][5][6][7][8][9][10]11,14,[16][17][18][19][20][21][22]26,…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the amount of glucose extracted (AGE) during chewing of gummy jelly is widely used in children, the elderly and denture wearers 2,6–8,10,12,14,16,17,19 . It has been reported that AGE increases proportionally with the amount of work 20 ; thus, a positive correlation is observed between the masticatory performance by the amount of glucose extracted and the masticatory performance by the sieving method 21 . AGE decreases with tooth loss 1,7 but increases after dental treatment 4,8,11,17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation